(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
Concepts such as “self-protection of the labor rights of the employee, implementation of the ongoing reforms in this regard, filling gaps in the legislation”, improvement of the current legal documents in this area, as well as self-protection of the labor rights of the employees It is dedicated to increasing efficiency using the latest information systems in the field of production, as well as analyzing foreign experience.